Braving the Wilderness: Developing a Polar Sense of Place - Fries-Gaither, Jessica (The Ohio State University Libraries, 2008)
The media can be accessed here: http://streaming.osu.edu/knowledgebank/digstory08/Fries-Gaither_Jessica.mp4 This short video provides an overview of the Arctic and Antarctic regions. It describes an increased understanding of the regions and the importance of developing a polar sense of place. The video was developed as part of the Beyond Penguins and Polar Bears project, an online magazine for elementary educators. The Beyond Penguins and Polar Bears project is funded by the National Science Foundation. Ohio State University. College of Education and Human Psychology National Science Foundation The Digital Union at The Ohio State University